Upaya Meningkatkan Perkembangan Moral dan Agama Anak Usia Dini Melalui Syair Bahasa Jawa Krama - Siti Nurjanah; Nurlaili Dina Hafni; Liea Herlin; Fahimatul Ilmiyah (Alzam: Journal of Islamic Early Childhood Education, 2023)
This research is intended to answer the problems of religious and moral development in early childhood, erosion of character values, behavior, morals and manners as well as the beginning to fade away of Javanese culture. The formulation of the research problem is: (1) How is Javanese poetry krama implemented at RA Muslimat NU 02 Tuban for the 2022/2023 academic year? (2) How will the religious and moral development of children at RA Muslimat NU 02 Tuban improve for the 2022/2023 academic year?This research uses a classroom action research method with two cycle stages. The results of this research show that the application of Javanese krama poetry in improving children's religion and morals can be seen in terms of assessment and has experienced an increase of 87% in the COMPLETE category. As well as increasing the religious and moral development of children in the pre-cycle research carried out initially, the percentage obtained was 52.1%, and increased to a percentage of 60.8% after action was carried out in cycle I. However, because the results of this percentage did not meet the indicators of success achieved then action was carried out again in cycle II and obtained a percentage of 87% with a very good or complete predicate category.